2003
DOI: 10.1021/jf030009v
|View full text |Cite
|
Sign up to set email alerts
|

Normal Phase High-Performance Liquid Chromatography Method for the Determination of Tocopherols and Tocotrienols in Cereals

Abstract: The eight vitamers of vitamin E (alpha-, beta-, gamma-, and delta-tocopherols and -tocotrienols) have different antioxidant and biological activities and have different distributions in foods. Some cereals, especially oat, rye, and barley, are good sources of tocotrienols. A fast procedure for the determination of tocopherols and tocotrienols (tocols) in cereal foods was developed. It involves sample saponification and extraction followed by normal phase high-performance liquid chromatography (HPLC). The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
241
5
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 344 publications
(278 citation statements)
references
References 17 publications
25
241
5
2
Order By: Relevance
“…Tocopherols were extracted as described for cereal seeds by Panfili et al (2003), by grinding and homogenizing 25 mg of freeze-dried leaf material in 500 ml 100 % methanol. After 20 min of incubation at 30°C, the samples were centrifuged at 14,000 rpm for 5 min, the supernatant was transferred to new tubes, and the pellet was re-extracted twice with 250-μl 100 % methanol at 30°C for 30 min, pooling all supernatants.…”
Section: Tocopherol Extraction and Measurementmentioning
confidence: 99%
“…Tocopherols were extracted as described for cereal seeds by Panfili et al (2003), by grinding and homogenizing 25 mg of freeze-dried leaf material in 500 ml 100 % methanol. After 20 min of incubation at 30°C, the samples were centrifuged at 14,000 rpm for 5 min, the supernatant was transferred to new tubes, and the pellet was re-extracted twice with 250-μl 100 % methanol at 30°C for 30 min, pooling all supernatants.…”
Section: Tocopherol Extraction and Measurementmentioning
confidence: 99%
“…It has also been suggested that xylanase in poultry diets improves gut health as indicated by reduced endogenous losses from the gastrointestinal tract (Bedford and Schulze, 1998). Wheat also contains about 75 mg of vitamin E (Panfili et al, 2003) and 2 mg of carotenoids (Hidalgo et al, 2006) per kg dry matter, which may contribute ABSTRACT. The study examined the effect of xylanase supplementation on apparent metabolizable energy (AME) and hepatic vitamin E and carotenoids in broiler chickens fed wheat based diets.…”
Section: Introductionmentioning
confidence: 99%
“…Extraction from each food sample was performed according to a previous procedure [17] with a small modification. Wet food sample (5.00 g), NaCl solution (1.80 mL, 10 g/L water), pyrogallol solution (200 μL, 6 g/L ethanol), and ethyl acetate (3.00 mL) were mixed in a 15-mL centrifuge tube and shaken vigorously.…”
Section: Extraction From Wet Food Samplementioning
confidence: 99%